Quadcopter Main Board Design with PID Algorithm as Controller - Bachtiar, Mochamad; Iwan Kurnianto Wibowo; Nur Cahyo Ihsan Prastyawan; Maretha Ruswiansari; Hendy Briantoro; Nofria Hanafi; Niam Tamami; Hendhi Hermawan; Eko Budi Utomo (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2022)
Kontes Robot Terbang Indonesia (KRTI) Flight controller division has a mission to independently make an unmanned aerial vehicle (UAV) controller. UAV controllers are usually made by non-local manufacturers, who have a package between the controller and the aircraft. Due to limited pins and specific functions, most controllers cannot adapt to user requirements. For this reason, in this study, we made a UAV controller with a more significant number of pins that can be programmed independently. Main Controller is a master board device used to control the stability of the UAV when flying. The main controller has been designed specifically for certain products so that the UAV cannot be modified. In this study, it is proposed to make the main controller that is specifically designed to fly a Quadcopter UAV. Movement control for quadcopter stability when flying using the Proportional Integral Derivative (PID) method. The main controller has a function that is to regulate the entire course of flight on unmanned vehicles. PID control can adapt to changes so that the system becomes stable. The PID control on the Main Controller is intended to balance the quadcopter concerning its orientation angle. The Main Controller is also tasked with recording data from sensors such as the Inertial Measurement Unit (IMU) and reading data from the remote. The controller successfully flew the quadcopter with a P value of 0.245, an I value of 0.0139, and a D value of 0.0085.